Dyskursy podstaw przedsiębiorczości - Pląsek, Rafał (Studia Edukacyjne, 2020)
The article discusses the discourses which describe entrepreneurship and market and state relations in the perspective of the social market economy in Polish Entrepreneurship Education textbooks. The author points out that dominant in the textbooks is the economic model of entrepreneurship. He also notes that the concept of social market economy, indicated in the Constitution of the Republic of Poland as the bedrock of the economic system, appears only in some textbooks.